Upaya Meningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Teams Games Tournaments (TGT) Berbantuan Media Prezi Dalam Materi Perakitan Komputer - Oktarika, Dini; Putri, Nur Fitriani Massilawati (Efektor, 2019)
The purpose of this study was to improve student learning outcomes using cooperative learning models Teams Games Tournaments type assisted by Prezi media in computer assembly material in multimedia X grade students of SMK Negeri 1 Sekadau Hilir Sekadau Regency. The method used in this study is the method of action research and the form of research is classroom action research with the use of cycles, where the stages of each cycle are planning, implementation, observation, reflection. Based on the results of the study, it was obtained 1) The teacher learning process in the first cycle of 66.67% was included in the "Active Enough" category and in the second cycle, 88.89% was included in the "Very Active" category. 2) The average learning outcomes of students using media games tournament assisted by media Prezi in the pre-action average value of 43.31 falls into the category of "Very Less" with classical completeness of 6.25% in the "Very Less" category. In the first cycle, the average value of 69.78 was included in the category "Fairly Good" with a value of classical completeness of 53.13% in the category of "Poor". In the second cycle, the average value was 79.84 in the category of "Good" with the classical completeness of 78.13% in the category of "Good". And for post-action, the average score is 87.09 in the category of "Very Good" with classical completeness of 90.63% in the category of "Very Good".